2013
DOI: 10.1371/journal.pone.0060185
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Suppression, DNA Methylation, and Histone Deacetylation of the Regulator of G-Protein Signaling 10 (RGS10) Gene in Ovarian Cancer Cells

Abstract: RGS10 regulates ovarian cancer cell growth and survival, and RGS10 expression is suppressed in cell models of ovarian cancer chemoresistance. However, the mechanisms governing RGS10 expression in ovarian cancer are poorly understood. Here we report RGS10 suppression in primary ovarian cancer and CAOV-3 ovarian cancer cells compared to immortalized ovarian surface epithelial (IOSE) cells, and in A2780-AD chemoresistant cells compared to parental A2780 cells. RGS10-1 and RGS10-2 transcripts are expressed in ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 47 publications
4
51
0
Order By: Relevance
“…Ovarian cancer is the leading cause of mortality from gynecological cancers and the fifth most common cause of cancer mortality among females (20). An increased understanding of the molecular and genetic changes causing ovarian cancer progression is likely to produce strategies to predict and prevent the occurrence of refractory disease.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer is the leading cause of mortality from gynecological cancers and the fifth most common cause of cancer mortality among females (20). An increased understanding of the molecular and genetic changes causing ovarian cancer progression is likely to produce strategies to predict and prevent the occurrence of refractory disease.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table IV (10,11,14,16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(29)(30)(31)(32)(33)(34)(35)(36)38,39,(41)(42)(43)(44)(45)(47)(48)(49)(50)(51)(52), we observed that a considerable number of DNA methylated genes, including MLH1, FBXO32, PROM1, RASSF1, PTEN, SFRP, TUBB3, L1TD1 and CLDN4, were associated with the invasion of ovarian cancer. Each gene was hypermethylated, resulting in the silencing of gene expression in ovarian cancer and drug-resistant tissue or cells and ultimately regulating tumour invasion.…”
Section: Correlation Analysis Of Ovarian Cancer Drug Resistance-relatmentioning
confidence: 54%
“…Among the 26 methylated genes, the methylation of ABCG2, Sulf-1, FANCF, CLDN4, TGFBI (63) and RGS10 (34) has been reported not to be associated with the prognosis of ovarian cancer. However, the methylation or abnormal expression of the remaining 20 genes are all statistically relevant to ovarian cancer prognosis.…”
Section: Correlation Analysis Of Ovarian Cancer Drug Resistance-relatmentioning
confidence: 99%
“…Previous studies have demonstrated that RGS10 gene transcription was suppressed due to epigenetic regulation by DNA methyltransferase-mediated hypermethylation in the gene promoter and the histone deacetylase 1-mediated reduction of histone acetylation in cancer cells. 31,32 In failing human hearts, the GpC island in RGS10 promoter is hypomethylated compared with normal hearts 33 ; in this case, the low expression of RGS10 in failing heart was less likely to be attributed to DNA methylation. However, we acknowledge that the association between histone deacetylase 1 and the RGS10 gene may be a potential mechanism for RGS10 reduction in hypertrophic hearts because class I HDACs (including histone deacetylase 1) are prominently prohypertrophic factors that induce cardiac hypertrophic response to AB or Ang II.…”
Section: Discussionmentioning
confidence: 93%